Preparation and thermal properties of mesoporous silica/phenolic resin nanocomposites via in situ polymerization - J. Lv; L. T. Meng; C. Wei; C. B. Yu; H. X. Liu (eXPRESS Polymer Letters)
In order to enhance the adhesion between inorganic particles and polymer matrix, in this paper, the mesoporous silica SBA-15 material was synthesized by the sol-gel method. The surface of SBA-15 was modified using γ-glycidyloxypropyltrimethoxysilane (GOTMS) as a coupling agent, and then mesoporous silica/phenolic resin (SBA-15/PF) nanocomposites were prepared via in situ polymerization. The structural parameters and physical properties of SBA-15, SBA-15-GOTMS (SBA-15 surface treated using GOTMS as coupling agents) and E-SBA-15/PF (SBA-15/PF nanocomposites extracted using ethanol as solvent) were characterized by X-ray diffraction (XRD), N2 adsorption-desorption, Fourier transform infrared spectroscopy (FTIR), scanning electron microscopy (SEM), transmission electron microscopy (TEM) and thermogravimetric analysis (TGA). The thermal properties of the nanocomposites were studied by differential scanning calorimetry (DSC) and thermogravimetric analysis (TGA). The results demonstrated that the GOTMS were successfully grafted onto the surface of SBA-15, and chemical bonds between PF and SBA-15-GOTMS were formed after in situ polymerization. In addition, it is found that the in situ polymerization method has great effects on the textural parameters of SBA-15. The results also showed that the glass transition temperatures and thermal stability of the PF nanocomposites were obviously enhanced as compared with the pure PF at silica contents between 1–3 wt%, due to the uniform dispersion of the modified SBA-15 in the matrix.